Methods of treatment of pulsating hematoma and false aneurysm peripheral arteries after endovascular interventions - Yu. A. Vinogradova; L. S. Kokov; I. P. Mikhailov; V. P. Kiryushchenkov; E. P. Troshkina (Лечащий Врач)
87 cases of peripheral artery false aneurysm and pulsating hematoma after endovascular interventions were analyzed. For all patients with pulsating hematoma, the treatment began with local compression with a pressure bandage. The compression efficiency was 89.2%. Attempts of local compression in patients with false aneurysms were not successful and all the patients were operated. Surgical treatment was effective in 100% of false aneurysm cases. The effectiveness of treatment was influenced by: the patient’s intake of anticoagulant and disaggregant drugs, constitutional features of the patient, arterial hypertension, localization and diameter of the postpuncture artery defect. Definitions of pulsating hematoma and false aneurysm of peripheral arteries are formulated.